Bryophytes in fragments of Terra Firme forest on the great curve of the Xingu River, Pará state, Brazil - (:unkn) unknown (Museu Paraense Emilio Goeldi, 2014)
Microclimatic conditions of tropical forest favour the high richness of bryophytes, which by being sensitive to environmental changes, are important indicators of habitat conditions. The aim of this study was to determine the richness and species composition of the bryophyte flora in fragments of terra firme forest on the great curve of the Xingu River, Pará state, Brazil. The collections were made in August and September 2012 in 14 fragments, in which were installed two plots per fragment, one at the edge and one inside, measuring 10 × 10 m each. The results showed 77 species in 45 genera and 18 families. Lejeunea setiloba Spruce and Marchesinia brachiata (Sw.) Schiffn. are new records for Pará state. The richness families in this study were the ones typically found in tropical forest surveys. A high richness of rare species in comparison to common ones, a pattern usually observed for plants in tropical forests was not reported in this study, probably due to historical fragmentation and disturbance in the area. The richness and species composition were determined mainly by the physiognomic characteristics of the studied forest fragments.
Briófitas em fragmentos florestais de terra firme na região da Volta Grande do Xingu, Pará, Brasil
Keywords: brioflora; Amazonian flora; liverworts; mosses; CNPQ::CIENCIAS BIOLOGICAS::BOTANICA